In‐Plane Detection of Guided Surface Plasmons for High‐Speed Optoelectronic Integrated Circuits. Issue 1 (24th November 2017) - Panchenko, Evgeniy; Cadusch, Jasper J.; Avayu, Ori; Ellenbogen, Tal; James, Timothy D.; Gómez, Daniel; Roberts, Ann
Abstract: Constrains on the speed of modern digital integrated circuits are dominated by the metallic interconnects between logic gates. Surface plasmon polaritons have potential to overcome this limitation and greatly increase the operating speed of future digital devices. Nevertheless, an ongoing issue is the compatibility of modern planar microelectronic circuits with current methods for detecting surface plasmons. Here, a new approach to in‐plane surface plasmon polariton detection is proposed and experimentally demonstrated. The design is based on metal–semiconductor–metal photodetectors that are acknowledged as having one of the best speed characteristics among photodetectors. In the design, the photodetector structure also plays a dual role as the outcoupling grating for surface plasmons, significantly reducing the footprint of the resulting device. The technique has the potential to enable the integration of surface plasmons as signal carriers in future high‐speed optoelectronic integrated circuits. Abstract : Constraints on the speed of modern digital integrated circuits are dominated by the metallic interconnects between logic gates. Surface plasmon polaritons can greatly increase the operating speed of digital devices. A novel in‐plane surface plasmon detection technique is demonstrated which could form a component of future high‐speed integrated circuits enabling advanced machine learning and artificial intelligence.